2021
DOI: 10.18494/sam.2021.3110
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Sensitivity Characteristics of Water Resources in Huai River Ecological–Economic Belt, China

Abstract: To achieve precision control of water resources in the Huai River Basin, the precision of the forecast and control of such resources must be improved. In the present study, a recharge method was applied to the basic data obtained from the quantitative forecast and precision control of water resources in the Huai River. In addition, the water balance method was used to analyze the spatiotemporal characteristics of the water resources in the Huai River ecological-economic belt (hereafter the eco-economic belt). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Between equally important and slightly more important = (2,3,4) Slightly more important = (3,4,5) Between slightly more important and rather important = (4,5,6) Rather important = (5,6,7) Between rather important and quite important = (6,7,8) Quite important = (7,8,9) Between quite important and extremely important = (8,9,10) Extremely important A pairwise comparison matrix A is obtained by pairwise comparison of any two factors. Accordingly, n(n−1)/2 pairwise comparisons are required for n factors in the index system.…”
Section: Fuzzy Number Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Between equally important and slightly more important = (2,3,4) Slightly more important = (3,4,5) Between slightly more important and rather important = (4,5,6) Rather important = (5,6,7) Between rather important and quite important = (6,7,8) Quite important = (7,8,9) Between quite important and extremely important = (8,9,10) Extremely important A pairwise comparison matrix A is obtained by pairwise comparison of any two factors. Accordingly, n(n−1)/2 pairwise comparisons are required for n factors in the index system.…”
Section: Fuzzy Number Meaningmentioning
confidence: 99%
“…Since China proposed the planning scheme of the Huaihe River Eco-economic Belt, this region has become an important practice place for territorial space development due to its abundant and concentrated ecological resources and low land-use intensity [5,6]. From the perspective of evaluation object, the studies on resource and environment carrying capacity include not only single classification but also comprehensive investigations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As the core city of the Huaihe River Eco-economic Belt, Huai'an City is located in the north-central part of Jiangsu, in the middle and lower reaches of the Huaihe River Basin, and is known as the Flood Corridor [29][30][31]. For this reason, this study selected Huai'an City for empirical research, and the scope of the study area is shown in Figure 1.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Currently, many studies on ecological sensitivity evaluation have been reported and were mainly focused on the following aspects: (1) ecological sensitivity evaluation of a certain region, such as Jianghan Plain, China [1], Three Gorges Reservoir Area in China [2], Denizli Province, Turkey [3], Pingtan Island (China) and Nile Delta (Egypt) [4], along the Yangtze River in China [5], etc. ; (2) Special research should be conducted on sensitive factors, such as soil erosion [6][7][8], geological disasters [9][10][11][12], cultivated land resources [13][14][15], and water resources [16][17][18]; (3) Spatial planning or spatial pattern optimization based on ecological sensitivity analysis, such as the optimization of spatial patterns of resource-based cities [19], optimization of land use spatial patterns [20], urban development boundary planning [21], landscape spatial planning [22], etc. ; (4) Ecological sensitivity evaluations of specific projects, such as power grid projects [23], airport reclamation projects [24], and hydroelectric power plant projects [25].…”
Section: Introductionmentioning
confidence: 99%